(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Aluminium Phosphide (ALP) is widely used in India as a fumigant to protect stored grains from pests and rodents. It is marketed in India as 3 gms tablets under several brand names such as Celphos, Phostek, Quickphos, Alphos, Phostoxin, and so on. ALP has the advantage of being cheap, efficacious, easy to use and freely available in the market. The incidence of poisoning has been steadily increasing and it is now the commonest poisoning method used in northern and central regions of the country. The toxic principle of ALP Phosphine causes hypoxia at the cellular level and causes death by multi-system failure. The effects of ALP on serum magnesium and the role of Intravenous magnesium sulphate as an antidote has been a topic of much debate. The present study was conducted with the aim of analysing the serum magnesium changes in cases of ALP poisoning.